The Jurassic of Denmark and Greenland: The Middle Jurassic of western and northern Europe: its subdivisions, geochronology and correlations - Callomon, John H. (Geological Survey of Denmark and Greenland, 2003)
The palaeogeographic settings of Denmark and East Greenland during the Middle Jurassic are outlined. They lay in the widespread epicontinental seas that covered much of Europe in the post-Triassic transgression. It was a period of continuing eustatic sea-level rise, with only distant connections to world oceans: to the Pacific, via the narrow Viking Straits between Greenland and Norway and hence the arctic Boreal Sea to the north; and to the subtropical Tethys, via some 1200 km of shelf-seas to the south. The sedimentary history of the region was strongly influenced by two factors: tectonism and climate. Two modes of tectonic movement governed basinal evolution: crustal extension leading to subsidence through rifting, such as in the Viking and Central Grabens of the North Sea; and subcrustal thermal upwelling, leading to domal uplift and the partition of marine basins through emergent physical barriers, as exemplified by the Central North Sea Dome with its associated volcanics. The climatic gradient across the 30º of temperate latitude spanned by the European seas governed biotic diversity and biogeography, finding expression in rock-forming biogenic carbonates that dominate sediments in the south and give way to largely siliciclastic sediments in the north. Geochronology of unrivalled finesse is provided by standard chronostratigraphy based on the biostratigraphy of ammonites. The Middle Jurassic saw the onset of considerable bioprovincial endemisms in these guide-fossils, making it necessary to construct parallel standard zonations for Boreal, Subboreal or NW European and Submediterranean Provinces, of which the NW European zonation provides the primary international standard. The current versions of these zonations are presented and reviewed.